2007
DOI: 10.3390/medicina43120125
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and waiting time to pregnancy: results of a pilot study

Abstract: Raktažodžiai: nėštumo laukimo laikas, reprodukcinė sveikata, rūkymas. Santrauka. Nėštumo laukimo laikas yra svarbus žmogaus reprodukcinės sveikatos rodiklis, kuris iki šiol Lietuvoje nebuvo tirtas. Duomenys apie nėštumo laukimo laiką buvo surinkti iš 111 moterų, kurios gimdė Klaipėdos ligoninės Akušerijos departamente, ligos istorijų. Septynios moterys, kurios pastojo po nevaisingumo gydymo, nebuvo įtrauktos į analizę, o likusių 104 moterų duomenys buvo analizuoti. Mes vertinome nėštumo laukimo laiko priklauso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In the investigation of menstrual cycle characteristics (start age, regularity and period duration) in both groups, it was found that menstrual regularity in both groups had significant difference that was consistent with the study of Idrovo et al, [15]. However, in the study of Zilaitiene et al, menstrual cycle regularity didn't have significant association with TTP [8].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In the investigation of menstrual cycle characteristics (start age, regularity and period duration) in both groups, it was found that menstrual regularity in both groups had significant difference that was consistent with the study of Idrovo et al, [15]. However, in the study of Zilaitiene et al, menstrual cycle regularity didn't have significant association with TTP [8].…”
Section: Discussionsupporting
confidence: 79%
“…Also, in the study performed by Spinelli, intercourse frequency ≥ 6 times per month reduced TTP [11]. However, in the study performed by Zilaitiene, intercourse frequency didn't have significant association with TTP [8]. Hassan et al didn't support the theory that frequent or scheduled intercourse can increase fertility chance and it was in consistent with other studies [3].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations